Optimization of AC / DC Hybrid Distributed Energy System with Power Electronic Transformer. (February 2019) - Guo, Shiqi; Mu, Yunfei; Jia, Hongjie; Chen, Naishi; Pu, Tianjiao; Yuan, Xiaodong
Abstract: This paper presents a new method of optimizing the distributed energy of AC/DC hybrid microgrids with power electronic transformer. Firstly, the steady state model of power electronic transformer in normal operation mode is proposed. Subsequently, for the AC/DC hybrid system with power electronic transformer, optimizing the scheduling model in order to achieve the full disposition of distributed energy in AC/DC hybrid system and economic optimization. Ultimately, with the case to verify the AC/DC power system model with power electronic transformer, the results show that: as the application of power electronic transformer in AC/DC hybrid system, the power transfer between the AC network and the DC network is controlled by the power regulation function of the power electronic transformer, which can effectively realize the full disposition of distributed generation. In addition, through the rational distribution power generation application, the operating costs of the system is reduced, which can achieve the economic operation of hybrid AC/DC system.